The Urgency of Refugee Legislation in Indonesia and the Present Obstacles - Riyanto, Sigit (Indonesian Journal of International Law, 2004)
Throughout the world and over the centuries, societies have welcomed frightened, weary foreigners, the victims of persecution and violence in their place of habitual residence. Basically every State has the responsibility of protecting refugees and asylum seekers within its teritory. Protection of refugees and asylum seekers is a classical issue in International Law. Nowadays more than 140 States have adopted International Instruments of Refugee Law. Eventhough the right to seek asylum has been enshrined in the Indonesian Consitution and the Human Rights Act ; up to nowadays Indonesia has not adopted any International Instrument of Refugee Law and has no national operative legislation dealing with the protection of refugee and asylum seeker. The objective of this paper was to discuss the urgency and the stumbling blocks of incorporating International Instruments of Refugee Law into the Indonesian Law. It should be born in mind that a national legislation concerning the protection of refugees and asylum seekers indicate commitment of a State to the protection of refugees and asylum seekers indicate commitement of a State to the protection and promotion of Human Rights in general. An incorporation of refugee law into the Indonesian Legal System would fill the gap concerning the unavailability of operational legal instrument dealing with refugee and asylum seeker in Indonesia.